The Arizona raiders - Hogan, James, 1891-1943.; Crabbe, Buster, 1908-; Hatton, Raymond, 1887-1971.; Hunt, Marsha, 1917-; Rhodes, Jane.; Downs, Johnny, 1913-; Withers, Grant, 1905-1959.; Grey, Zane, 1872-1939.; Favorite Films Corporation; Lions Gate Home Entertainment (Santa Monica, California : Lions Gate Entertainment, 2006)
A drifter escapes being hanged by a lynch mob and flees to Wyoming with his sidekick. A wealthy horse rancher and her sister hire them and romance blooms. Meanwhile the ranch is plagued by rustlers and the drifter is being blamed by the real perpetrator, the town's conniving attorney.
Originally released as a motion picture in 1936.
Full screen presentation (1.33:1)
Based on the novel "Raiders of Spanish Peaks" by Zane Grey.
Special features: True stories of Zane Grey: Outdoor adventures with an introduction by Loren Grey ; Fisherman's pluck ; An American legend.
Photographer, Leo Tover ; editor, Chandler House.
Larry "Buster" Crabbe, Raymond Hatton, Marsha Hunt, Jane Rhodes.
Keywords: Drifters -- Drama; Cattle stealing -- Wyoming -- Drama; Ranch life -- Wyoming -- Drama; Feature films -- United States; DVD-Video discs; Western films; Film adaptations